Non-Keratinizing Sinonasal Squamous Cell Carcinoma Extending to the Skull Base: Surgical Management with Total Maxillectomy - A Case Study - Anak Agung Wira Ryantama; Eka Putra Setiawan; Wayan Lolik Lesmana; Agus Rudi Asthuta; Komang Andi Dwi Saputra; Luh Sartika Sari (HM Publisher, 2025)
Sinonasal squamous cell carcinoma (SNSCC) is an uncommon malignancy arising within the nasal cavity and paranasal sinuses, representing approximately 3% of head and neck cancers. The non-keratinizing subtype (NKSCC) presents unique diagnostic and therapeutic challenges, particularly when exhibiting locally advanced disease with extension towards critical structures like the skull base. Management typically involves a multimodal approach centered around surgical resection, often followed by adjuvant therapy. We present the case of a 51-year-old female, employed in the wood furniture industry, presenting with a progressively enlarging right nasal mass initially noted four years after removal of a right cheek lesion. Symptoms included unilateral nasal obstruction, epistaxis, anosmia, and loosening of maxillary teeth. Clinical examination revealed a large, friable mass obliterating the right nasal cavity and extending onto the palate. Computed tomography confirmed an extensive destructive mass involving the right nasal cavity, maxillary sinus, ethmoid sinus, extending to the nasopharynx, parapharyngeal space, masticator space, buccal space, frontal sinuses, and abutting the right internal carotid artery. Biopsy confirmed Non-Keratinizing Squamous Cell Carcinoma. The patient was staged as T4bN2cM0 according to the AJCC 8th edition criteria. Following neoadjuvant chemotherapy, the patient underwent total maxillectomy via a Weber-Ferguson approach with Lynch modification, including placement of a dental obturator. In conclusion, advanced NKSCC involving the skull base requires aggressive, multidisciplinary management. This case highlights the necessity of radical surgical resection, such as total maxillectomy via extended approaches like the Weber-Ferguson with Lynch modification, to achieve oncologic control in extensive T4b disease. Despite the challenges posed by proximity to vital structures, surgery remains the cornerstone of treatment, often requiring adjuvant therapy to optimize outcomes. Long-term follow-up is crucial due to the inherent risk of recurrence.